ORC- and Cdc6-dependent complexes at active and inactive chromosomal replication origins in Saccharomyces cerevisiae. - Santocanale, C (1996)
We have developed a genomic footprinting protocol which allows us to examine protein-DNA interactions at single copy chromosomal origins of DNA replication in the budding yeast Saccharomyces cerevisiae. We show that active replication origins oscillate between two chromatin states during the cell cycle: an origin recognition complex (ORC)-dependent post-replicative state and a Cdc6p-dependent pre-replicative state. Furthermore, we show that both post- and pre-replicative complexes can form efficiently on closely apposed replicators. Surprisingly, ARS301 which is active as an origin on plasmids but not in its normal chromosomal location, forms ORC- and Cdc6p-dependent complexes in both its active and inactive contexts. Thus, although ORC and Cdc6p are essential for initiation, their binding is not sufficient to dictate origin use.